Functions, Theories And Practice Of Administrative Law In Contemporary Governance - Babajide Olatoye Ilo (Fakultas Hukum Universitas Lampung, 2022)
The vast development in the socio, economic and political spheres of the contemporary society makes governance more demanding and cumbersome. This necessitates the rational for a system of administration where governmental powers and functions can legally be delegated to individuals and or corporate bodies otherwise known as administrative bodies to carry out the functions and powers of Government in modern society. Governmental powers and functions are traceable to the Constitution which provides the limits of such powers. Administrative agencies saddled with the responsibility of performing the functions of Government must be properly created and must at all times act within the scope of power created by the enabling law. Abuse by the administrative agencies in the exercise of their functions is inevitable, and hence this research through doctrinal methodology examines the system of law that oversees the internal operations of Government agencies through developments of administrative law principles. Although various theories in administrative law like red, green and amber light have emerged over the years with conflicting arguments, the court are nonetheless always ready to grant remedies to an aggrieved citizen whenever the administrative agencies exceed or abuse its powers.